PEMODELAN PRODUKTIVITAS HYDRAULIC STATIC PILE DRIVER MENGGUNAKAN MODEL ANALITIS PADA TANAH BERLANAU - Warsito, Joko Yulianto Eko; Hatmoko, Jati Utomo Dwi (JEMIS (Journal of Engineering & Management in Industrial System), 2016)
Rapid urban growth has caused an increase of infrastructure and building construction projects in recent years in terms of project scale and number. Many of which certainly involve the construction of deep foundation, including pile foundation. In particularly densely populated urban areas, the need for more environmentally friendly pile driving equipment, such as hydraulic static pile driver (HSPD), is therefore inevitable. The aim of this study is to give a problem solving about HSPD productivity using analytical model. The objective of this study is to produce curves model of HSPD productivity. An analytical model has been designed utilizing 252 data of point piling from the four projects and simulation, i.e. size of driven piles, piling depth, and cycle time. The result of model is nomogram of HSPD productivity against piling depth for 3 driven pile size such as equilateral triangle 32 cm, square 25 cm, and square 30 cm. The model average validity is 96.07% and deviation standard is 2.32%. The sensitivity value 95.154% for equilateral triangle 32 cm, 9.376 for square 25 cm, and 94.298% for square 30 cm of driven pile.